Narodnostno neopredeljeno prebivalstvo ob popisih 1991 in 2002 v Sloveniji - Repolusk, Peter (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2006)
The article deals with the ethnically undefined population within the territory of the Republic of Slovenia in the time of the population censuses 1991 and 2002. It consists of more statistical categories: the ethnically undeclared, the category unknown and the category of persons that decide not to answer to the question on ethnic heritage. In the last twenty years demographic changes concerning ethnically undefined groups had the most important role on the changes of the overall ethnic structure in the country. In last decade especially category unknown shows a substantial increase in number.
Keywords: demogeografija; popis prebivalstva; demografska statistika; etnična struktura; Slovenia; Slovenija; 1991; 2002